Bijective Single Valued Neutrosophic Graph and Its Application in Fraud Detection Analysis in Social Networks - D.Rajalaxmi; R.Shivaragavi; Said Broumi (Neutrosophic Sets and Systems)
In this paper, a new concept of bijective single valued neutrosophic set and bijective single valued neutrosophic graphs are introduced. Also, the height, depth, bijective single valued neutrosophic bridge (BSVN – Bridge), bijective single valued neutrosophic cut vertex (BSVN – cut vertex) in bijective single valued neutrosophic graphs are defined. Some properties of bijective single valued neutrosophic cycles have been explored. Relation between Connectivity and BSVN-cut vertices, BSVN-Bridges are given. It contains few significant properties like, if  = dE , then  is not a BSVN-bridge. Also, If  = dE , being an edge in a BSVN-cycle graph G of length n , then G has (n −1) BSVN-bridges. An application of BSVN graphs by considering the users as vertices and interaction between the users as edged in an instagram social network is used in fraud detection analysis in social networks by using almost all the properties which were explored related to cycles.